Preparation method of tannic acid-based marine concrete chloride ion-resistant environment-friendly coating
The one-step method of preparing tannin acid-based marine concrete anti-chlorine ion environmentally friendly coating solves the problem of toxic substances and prone to aging and falling off during the production process, and achieves a green, environmentally friendly and cost-effective anti-corrosion effect of marine concrete. , significantly improves chlorine resistance and reduces costs.
Patent Information
- Application Number
- CN202411513558.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-07
AI Technical Summary
The existing marine concrete anti-corrosion coating produces toxic substances during the production process and is prone to aging and falling off, causing harm to the environment and human health, and is costly, making it difficult to achieve a green, environmentally friendly and cost-effective alternative.
A one-step method is used to prepare a tannin-based marine concrete anti-chlorine ion environmentally friendly coating. By preparing a mixed aqueous solution of tannin and ferric nitrate and aqueous sodium hydroxide solution, adjust the pH value and stir to form a tannin-trivalent ferrous ion film. The layer is repeated to improve the chlorine resistance of the coating.
It significantly improves the anti-chlorine ion capacity of concrete, reduces the electric flux value, and costs only one-third of the epoxy coating. It is environmentally friendly, with excellent anti-chlorine and anti-corrosion performance and cost-effective advantages.
Smart Images

Figure CN119263885A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of concrete protection, and mainly relates to a one-step-based tannic acid-based marine concrete chloride ion-resistant environmentally friendly coating and a preparation method thereof. Background Art
[0002] As one of the most widely used building materials in the world, concrete is widely used in engineering. Due to the high chloride content in the marine environment, the steel bars are depassivated under the action of chloride ions, which leads to the rust expansion of steel bars, cracking of concrete and even falling off. In order to improve the durability of reinforced concrete, on the one hand, the concrete structure itself can be improved by rationally selecting raw materials such as cement, mineral admixtures, aggregates and admixtures; on the other hand, for reinforced concrete structures in harsh service environments, additional anti-corrosion measures such as corrosion inhibitors, rust inhibitors and anti-corrosion coatings can be used for additional protection. Among the above measures, anti-corrosion coatings stand out with their long service life and simple construction and maintenance. At present, the anti-corrosion coatings used in ports and offshore projects are mainly synthetic organic coatings such as epoxy. Some of the raw materials and by-products in the production process are toxic substances, and the coatings cannot be degraded after peeling off, which will cause irreversible harm to human health and the ecological environment.
[0003] At present, people pay more attention to ecological environment protection. It is imperative to develop a new type of marine concrete anticorrosion coating that is green, environmentally friendly, economical and efficient. This is an urgent task for protecting the marine environment and achieving sustainable development. Inspired by the adhesion behavior of bivalve mollusks such as mussels, studies have found that dopamine plays an important role in the adhesion of mussels. The catechol group and amino group in it enable it to adhere to various organic and inorganic surfaces through covalent bonds and non-covalent interactions, and then it is widely used in surface modification and coatings. However, dopamine is relatively expensive and difficult to promote and apply on a large scale. Compounds containing catechol groups are widely present in nature. Among them, tannic acid, which is widely available and inexpensive, has been widely used in medicine, food, daily chemicals, etc. The pyrogallol group makes it have similar chemical properties to dopamine, thereby improving the chlorine resistance of concrete. Summary of the invention
[0004] The purpose of the present invention is to provide a one-step method for preparing a tannic acid-based marine concrete chloride ion-resistant environmentally friendly coating, which has the advantages of being green and environmentally friendly and having a significant chloride-resistant effect. In order to achieve the above-mentioned purpose of the invention, the present invention provides the following technical solutions:
[0005] A method for preparing a tannic acid-based marine concrete chloride ion-resistant environmentally friendly coating based on a one-step method comprises the following steps:
[0006] 1) preparing a mixed aqueous solution of tannic acid and ferric nitrate and a sodium hydroxide aqueous solution, wherein the mass ratio of tannic acid to ferric nitrate in the mixed aqueous solution of tannic acid and ferric nitrate is 40:(12-18);
[0007] 2) Place the concrete part in a mixed aqueous solution of tannic acid and ferric nitrate, adjust the pH to 7.8-8.2 with a sodium hydroxide aqueous solution, take out the concrete part after stirring for a period of time, and remove excess tannic acid and ferric nitrate.
[0008] 3) Repeat step 2) at least once, and the tannic acid-based marine concrete anti-chloride ion environmentally friendly coating prepared by the one-step method is completed.
[0009] Furthermore, in step 1), the mass ratio of tannic acid to ferric nitrate is 40:15.
[0010] Furthermore, the concentration of the sodium hydroxide aqueous solution is not higher than 0.5 mol / L.
[0011] Further, in step 2), the period of time is 1 minute, and in step 3), step 2) is repeated ten times.
[0012] At present, the anti-corrosion coatings used in ports and offshore projects are mainly artificial synthetic organic coatings such as epoxies. These coatings are prone to aging and falling off, and will produce toxic substances during production or use, thereby polluting the environment. The present invention is a mussel bionic environmentally friendly concrete anti-corrosion coating based on tannic acid, which has the advantages of being derived from nature, environmentally friendly, having a significant anti-chlorine effect, and being economical and efficient. By conducting an electric flux test to test the concrete's anti-chloride ion ability of the coating of the present invention, and comparing it with other coatings, it was found that under the unit thickness of the coating of the present invention, compared with the uncoated concrete, the electric flux value per micron of the coating is reduced by up to 52.17%, which is 79 times that of other commonly used commercial coatings such as epoxy resins; at the same time, the material cost of the coating of the present invention per square meter in China is US$3.29, which is only about one-third of that of epoxy coatings, and has outstanding advantages in both performance and cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Coating flow chart of tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on one-step method
[0014] Figure 2 Scanning electron microscope image of the cross section of tannic acid-based marine concrete chloride ion-resistant environmentally friendly coating based on a one-step method
[0015] Figure 3 Fourier transform infrared spectroscopy results
[0016] Figure 4 X-ray photoelectron spectroscopy results
[0017] Figure 5 Percentage reduction of electric flux value under different coating unit thickness DETAILED DESCRIPTION
[0018] The present invention is a one-step method for preparing a tannic acid-based marine concrete chloride ion resistant environmentally friendly coating, which can effectively resist chloride salt corrosion and is green, environmentally friendly, economical and efficient.
[0019] The present invention provides a tannic acid-based marine concrete chloride ion-resistant environmentally friendly coating based on a one-step method and a preparation method thereof (Example 1), which is now described in conjunction with a specific example and comprises the following steps:
[0020] Example 1
[0021] 1) After the concrete curing is completed, take out the concrete specimen, rinse the surface of the specimen with distilled water three times, scrape off the floating slurry, and then dry it.
[0022] 2) Prepare a 0.4 g / L tannic acid aqueous solution: weigh tannic acid powder using an electronic balance, dissolve it in distilled water, and stir thoroughly to obtain a 0.4 g / L tannic acid aqueous solution.
[0023] 3) Prepare a 0.15 g / L ferric nitrate aqueous solution. Weigh ferric nitrate crystals using an electronic balance, dissolve them in distilled water, and stir thoroughly to obtain a 0.15 g / L ferric nitrate aqueous solution.
[0024] 4) Prepare a 0.1 mol / L sodium hydroxide aqueous solution, weigh sodium hydroxide powder using an electronic balance, quickly add distilled water, and stir thoroughly to obtain a 0.1 mol / L sodium hydroxide aqueous solution.
[0025] 5) Place the concrete specimen in a measuring cup, add sufficient tannic acid aqueous solution and ferric nitrate aqueous solution at a volume ratio of 1:1, quickly adjust the pH to 8.0 with sodium hydroxide aqueous solution, stir for 1 minute, then take out the concrete specimen and rinse it with distilled water to remove excess tannic acid and ferric nitrate. In this process, the oxidative self-polymerization reaction of tannic acid and the coordination of iron ions / hydroxyl groups occur simultaneously. The iron ions strengthen the bonding force of the molecules in the tannic acid-based coating, and directly form a tannic acid-trivalent iron ion membrane layer in one step.
[0026] 6) Repeat the above step 5) 10 times, then rinse the concrete specimen with distilled water and dry it. Thus, the tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on the one-step method is prepared, and the coating can protect the marine concrete from chloride salt corrosion.
[0027] Comparative Example 1
[0028] According to the "Preparation method of chloride ion resistant concrete coating based on tannic acid and iron ion coordination" (authorization announcement number CN111286221B), the corresponding anti-corrosion coating is prepared. Figure 5 The “multi-step method”.
[0029] Comparative Example 2
[0030] The concentration of the tannic acid aqueous solution used is 2g / L, and the concentration of the sodium hydroxide aqueous solution is 0.1mol / L. Put the concrete specimen into a measuring cup, add a sufficient amount of tannic acid aqueous solution, quickly adjust the pH to 7.8 with sodium hydroxide aqueous solution, and add a magnetic bar to the bottom of the measuring cup. Stir for 24 hours, then take out the concrete specimen and rinse it with distilled water to remove excess tannic acid. At this point, the coating preparation is complete, corresponding to the instructions attached Figure 5 "Oxidative self-polymerization method".
[0031] Comparative Examples 3 to 8 are all traditional commercial anti-corrosion coatings, corresponding to the appendix of the specification. Figure 5 “Acrylic A”, “Chlorinated rubber B”, “Epoxy resin A”, “Polymer emulsion B”, “Polyurea elastomer”, “Polyurethane B”.
[0032] Figure 1 , Figure 2 , Figure 3 , Figure 4 and Figure 5 They are respectively the coating flow chart of tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on one-step method, the scanning electron microscope picture of the cross section of tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on one-step method, the Fourier transform infrared spectrum results of the coating, the X-ray photoelectron energy spectrum results of the coating, and the percentage reduction of the electric flux value under different unit thickness of the coating.
[0033] Figure 1 The process of preparing tannic acid-based chloride ion-resistant and environmentally friendly coating for marine concrete based on a one-step method is demonstrated.
[0034] Figure 2 This is a scanning electron microscope photograph of the cross-section of a specimen coated with a tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on a one-step method. From the figure, it can be observed that a thin layer of coating covers the surface of the concrete specimen. Through measurement, the average thickness of the coating is about 0.6μm.
[0035] Figure 3 The ATR-FTIR results of the uncoated concrete specimen and the one-step tannic acid-based marine concrete anti-chloride ion environmentally friendly coating are shown in Figure 2. For the uncoated concrete specimen, the spectral line ~3440cm -1 Hydroxide ion (OH - ) absorption peak, ~2925cm -1 and ~1480cm -1 is the absorption peak of carbonate substances in cement mortar, and ~1009cm -1is the absorption peak of sulfate substances; for the tannic acid-based marine concrete anti-chloride ion environmentally friendly coating concrete specimen based on the one-step method, ~3440cm -1 The absorption peak at 2925 cm is the absorption peak of the hydroxyl group (-OH) in the tannic acid molecule. -1 The absorption peak is the carbonate substance, which may be the carbonate substance in the cement mortar component that was scraped off with the coating during the sampling process. In addition, there is a characteristic peak belonging to tannic acid, ~1795cm -1 and ~1436cm -1 They are the stretching vibration peaks of the carbonyl group (C=O) in the tannic acid molecule and the carbon-carbon double bond (C=C) on the aromatic ring, 1085 cm -1 and 1020cm -1 The absorption peak at 626 cm is the stretching vibration peak of the C-OH group. -1 The absorption peak at is the stretching vibration peak of the Fe-O group. From the ATR-FTIR results, it can be seen that the tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on the one-step method has been successfully prepared on the concrete surface.
[0036] Figure 4 The XPS results of uncoated concrete specimens and tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on a one-step method. (a)-(d) are the Fe 2p spectrum of uncoated concrete specimens, the Fe 2p spectrum of tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on a one-step method, the O1s spectrum of uncoated concrete specimens, and the O1s spectrum of tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on a one-step method. It can be seen from the Fe 2p spectrum that the Fe 2p in the uncoated concrete specimen is 3 / 2 The main peak is located at about 712eV, and the peak separation is 14eV; Fe 2p in concrete specimens of tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on one-step method 3 / 2 The main peak moved to 711eV, and the peak separation was 14eV. In the O1s spectrum, the O1s peak in the uncoated concrete specimen can be divided into three peaks: 530.5eV, 531.7eV, and 532.4eV, which are respectively attributed to the Si-O-Ca, Si-OH, and Si-O-Si groups in the cement mortar; the O1s peak in the tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on the one-step method can be divided into two peaks: 531.2eV and 533eV, of which 531.2eV is Fe-O in the complex formed by the coordination of tannic acid and iron ions, and 533eV can be attributed to Fe-OH therein. From the XPS results, it can be seen that the tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on the one-step method has been successfully prepared on the concrete surface.
[0037] Figure 5The percentage reduction of the electric flux value under different unit thickness of the coating is shown. When the thickness of the coating is considered, since the tannic acid-based marine concrete anti-chloride ion environmentally friendly coating based on the one-step method is thin and dense, its anti-chlorine effect under unit thickness is significantly better than other types of coatings. The coating of the present invention can reduce the electric flux by 52.17% per micron, which is 79 times that of commonly used commercial coatings such as epoxy resins, while the percentage reduction of electric flux per micron of other commercial coatings does not exceed 1.6%. It can be seen that the coating of the present invention is very advantageous in terms of "efficiency". At the same time, compared with the invention patent "Preparation method of anti-chloride ion concrete coating based on tannic acid and iron ion coordination" (authorization announcement number CN 111286221 B), the unit thickness anti-chlorine effect of the coating of the present invention is more than 4 times its anti-chlorine effect, which further proves that the coating of the present invention has excellent anti-chlorine and anti-corrosion properties.
[0038] The thickness of the embodiments and comparative examples and the percentage of electric flux reduction per unit thickness are shown in Table 1.
[0039] Table 1 Thickness of the embodiments and comparative examples and percentage of electric flux reduction value per unit thickness
[0040]
[0041]
[0042] As can be seen from Table 1, the coating of the present invention (Example 1) has a thickness of only 0.6 μm, and its anti-chlorine effect per unit thickness is more significantly better than other types of coatings. The coating of the present invention can reduce the electric flux by 52.17% per micron, which is 79 times that of commercial coatings such as commonly used epoxy resins, while the electric flux reduction percentage per micron of other commercial coatings does not exceed 1.6%. At the same time, compared with the invention patent "Preparation method of anti-chlorine ion concrete coating based on tannic acid and iron ion coordination" (authorization announcement number CN111286221B), that is, "multi-step method", the unit thickness anti-chlorine effect of the coating of the present invention is more than 4 times its anti-chlorine effect, which more fully proves that the coating of the present invention has excellent anti-chlorine and anti-corrosion performance. In terms of price, the material cost of the coating of the present invention per square meter in China is 3.29 US dollars, which is about half of its cost and about one-third of epoxy coatings. The above two aspects are sufficient to prove that the coating of the present invention effectively improves the anti-chlorine performance of concrete under the premise of environmental protection, and has a strong value for promotion and application.
[0043] The above description is only a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a tannic acid-based marine concrete chloride ion-resistant environmentally friendly coating based on a one-step method, comprising the following steps: 1) preparing a mixed aqueous solution of tannic acid and ferric nitrate and a sodium hydroxide aqueous solution, wherein the mass ratio of tannic acid to ferric nitrate in the mixed aqueous solution of tannic acid and ferric nitrate is 40:(12-18); 2) Place the concrete part in a mixed aqueous solution of tannic acid and ferric nitrate, adjust the pH to 7.8-8.2 with a sodium hydroxide aqueous solution, take out the concrete part after stirring for a period of time, and remove excess tannic acid and ferric nitrate. 3) Repeat step 2) at least once, and the tannic acid-based marine concrete anti-chloride ion environmentally friendly coating prepared by the one-step method is now completed.
2. The method for preparing the tannic acid-based marine concrete chloride ion resistant environmentally friendly coating according to claim 1, characterized in that: In step 1), the mass ratio of tannic acid to ferric nitrate is 40:
15.
3. The method for preparing the tannic acid-based marine concrete chloride ion resistant environmentally friendly coating according to claim 1, characterized in that: The concentration of the sodium hydroxide aqueous solution is not higher than 0.5 mol / L.
4. The method for preparing the tannic acid-based marine concrete chloride ion resistant environmentally friendly coating according to claim 1, characterized in that: In step 2), the period of time is 1 minute, and in step 3), step 2) is repeated ten times.
Citation Information
Patent Citations
Preparation method of chloride ion resistant concrete coating based on tannic acid and iron ion coordination
CN111286221B